The Use of Prepositional Phrase-Based Bundles in Essays Written by Turkish Learners of English - Kaya, Ömer Faruk (IGI Global, 2025)
Lexical bundles (LBs) are frequently found in academic writing and have long been of interest to researchers, particularly in the context of L2 writers. Studies comparing L1 and L2 writing suggest that non- native writers use fewer and less diverse LBs than native speakers. Some studies suggest that this may be related to L2 learners’ use of contextually appropriate bundles that are spelled incorrectly or mistakenly confused with similarly spelled bundles. This chapter aims to contribute to these arguments by investigating the use of 4-word prepositional phrase- based lexical bundles by Turkish learners of English. To provide a more comprehensive analysis, the study includes both attempted and correctly used bundles in the frequency analysis results. The study also explores the relationship between LB frequency and writing quality. The findings show that Turkish learners use a limited variety of PP- based bundles compared to native speakers. It was also found that high-scoring essays do not necessarily contain a greater variety or quantity of LBs than low-scoring essays. These results highlight the need for targeted instructional strategies to improve L2 learners’ awareness of LBs. © 2025 by IGI Global Scientific Publishing.